Response to the impact of COVID-19 by health professions education institutions in Africa: a case study on preparedness for remote learning and teaching - Shalote Chipamaunga; Champion Nestai Nyoni; Mike Nantamu Kagawa; Quenton Wessels; Elliot Kafumukache; Rudo Gwini; Gwendoline Kandawasvika; Patricia Katowa-Mukwato; Rangarirai Masanganise; Rudo Nyamakura; Idah Nyawata; Louise Pretorius; et al. (Smart Learning Environments, 2023)
Abstract Background Africa, like other parts of the world, continuously strives to deliver quality health professions education. These efforts are influenced to a larger extent by the socio-economic and cultural context of the region, but also by what happens globally. The global disruption caused by the COVID-19 pandemic in 2020 necessitated the implementation of emergency remote teaching to continue delivering on the mandate of educating future health professionals. The purpose of this research was to describe the response of selected health professions education institutions in Southern Africa to the impact of COVID-19 and their preparedness for remote learning and teaching. Methods A case study design was applied using an adapted ADKAR model as a conceptual framework for data interpretation. The purposively selected study population consisted of educators, students, and administrators in undergraduate medical and nursing programmes from six institutions in five countries. Results A total of 1307 respondents provided data for the study. Many of the institutions were caught off-guard when most educators and almost all students were required to leave their universities and go home. Stakeholders immediately became aware of the need to adopt online approaches as an emergency measure. In all programmes, educators, students, and administrators agreed that change was desired, and students realised that they had to take charge of their own learning independently. Overall educators reported confidence in the ability to use of standard Microsoft software, while knowledge of learning management systems proved more challenging for both educators and students. Many stakeholders, especially students and administrators, reported uncertainty about their ability to function in the new reality. Conducive family dynamics, a quiet space to study, good connectivity, a reliable electricity supply and appropriate devices were reported to reinforce learning and teaching. Conclusions The findings highlight the need for higher education institutions to prepare for alternative modes to face-to-face learning and teaching approaches with the ultimate aim of transitioning to full online learning more expeditiously. This requires scaling up educational infrastructure, prioritising strategic directives driving continuous professional development of educators and fostering co-constructivist approaches towards student centered education.